EPEN-05. Adenosine receptor expression in paediatric ependymoma. (3rd June 2022) - Spanoudakis, Chelsea; Chapman, Rebecca; Paine, Simon; Grundy, Richard; Franks, Hester; Ritzmann, Timothy
Abstract: PURPOSE: Paediatric ependymoma is associated with dismal outcomes. Whilst understanding of its underlying biology has advanced, there has been little progress in treatment and clinical outcomes. Acting through four G protein-coupled receptors (encoded by ADORA1, ADORA2A, ADORA2B and ADORA3), adenosine is a signalling molecule often present at high levels in tumours. Adenosine signalling can aid tumour proliferation and invasiveness via mechanisms including suppression of tumour-infiltrating immune cells. Adenosine receptors therefore represent a potential therapeutic target in paediatric ependymoma, however neither levels nor patterns of expression have been previously reported. We hypothesised that adenosine receptors would be expressed in paediatric ependymoma and that this expression would vary between molecular subgroups. METHODS: Three publicly available gene expression datasets were analysed for adenosine receptor expression using Kruskal-Wallis, Mann-Whitney U and chi-square tests. RNAscope assays for adenosine receptors and CD68 were then performed on ten full-face ependymoma FFPE sections from posterior fossa A (PFA1 and PFA2) tumours to understand patterns of expression within ependymomas with the highest levels of expression identified by the gene expression datasets. RESULTS: Statistically significant differences were identified between adenosine-related genes across ependymoma subgroups of differing anatomical origin (supratentorial ZFTA-positive versus posterior fossa A and B (PFA/PFB)), with median adenosine-related gene levels generally higher in the PFA subgroup. Particularly, ADORA1, 2A, 2B and 3 gene expression was higher in PFA tumours than other subgroups. Analysis of the ten cases demonstrated measurable expression of all four adenosine receptors by RNAscope and patterns in the distribution and relative levels of expression of the adenosine receptors across PFA1 and PFA2 tumours were described. CONCLUSION: Using two different techniques we demonstrated that adenosine receptors are expressed in paediatric ependymomas. There are significant differences in level of expression between tumour subgroups. Adenosine receptors therefore represent a potential therapeutic target which should be explored further.